Comparison between the replacements of CH4 in natural gas hydrate with CO2 and NH3. (November 2021) - Li, Dongze; Chen, Lei; Liu, Gang; Xiao, Jingfeng; Li, Bingfan; Yu, Wenguang
Abstract: Natural gas hydrate (NGH), as a clean energy with great development potential, has been limited by the lack of efficient and safe exploitation methods for a long time. The CO2 displacement method proposed in recent years has not made substantial progress because of its poor permeability and low efficiency. The NH3 replacement method is proposed in this paper because of its strong permeability. We performed orthogonal molecular dynamics simulation of the replacement of CH4 in hydrate with NH3 and CO2 at different temperatures (245 K, 255 K, 265 K) and pressures (3 MPa, 5 MPa, 10 MPa). It is shown that:(1) Compared with CO2 molecules, NH3 and can penetrate into the hydrate layer effectively, and the resulting pore channels are conducive to the outward diffusion of CH4 molecules. (2) With the progress of the replacement process, the hydrate structure gradually decomposes but not completely, and the residual structure will inhibit the diffusion of CH4 molecules and lead to the agglomeration of CH4 molecules. (3) Within 1000 ps, the number of CH4 molecules replaced by NH3 is more than that of CO2 under the conditions of 245 K and 255 K, and less than that of CO2 under the conditions of 265 K. At the same temperature, the pressure does not affect the final comparison result.